Intellectual capital and high-tech firms' financing choices in the European context: a panel data analiysis - Sardo, Filipe (2020)
This paper seeks to analyse the relationships between listed high-tech firms' financing choices and intellectual capital (IC). It also analyses the impact of ownership concentration on IC investments in high-tech firms. The data set was gathered from the Datastream database for a sample of listed high-tech firms in 14 Western European countries for the period between 2004 and 2015. The data set has an unbalanced panel structure, with the number of years of observations on each firm varying between 3 and 12. We use dynamic panel data models, the GMM system (1998) estimator. Results suggest that internal finance and equity issues are positively while debt is negatively related to IC in high-tech firms. High-tech firms seem to rely on equity issues and internal finance, avoiding debt to fund IC assets. Ownership concentration is negatively related to IC investments in high-tech firms. To the authors' knowledge, this is the first study exploring the relationships between financing choices and IC in high-tech firms. The findings also contribute to the literature by analysing the impact of ownership concentration on IC investments of high-tech firms.